2020
DOI: 10.1124/jpet.120.265892
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Δ9-Tetrahydrocannabinol in Adolescent and Adult Male Mice

Abstract: We investigated the pharmacokinetic properties of D 9 -tetrahydrocannabinol (D 9 -THC), the main psychoactive constituent of cannabis, in adolescent and adult male mice. The drug was administered at logarithmically ascending doses (0.5, 1.6, and 5 mg/kg, i.p.) to pubertal adolescent (37-day-old) and adult (70day-old) mice. D 9 -THC and its first-pass metabolites-11hydroxy-D 9 -THC and 11-nor-9-carboxy-D 9 -THC (11-COOH-THC)-were quantified in plasma, brain, and white adipose tissue (WAT) using a validated isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 40 publications
(49 reference statements)
8
63
0
Order By: Relevance
“…Importantly, CB1Rs play a critical role in neuronal development due to their ability to modulate the release of neurotransmitters and expression, establishment of synaptic connection ( Kano et al, 2009 ), and epigenetic regulation ( Prini et al, 2018 ). The pharmacological exogenous manipulation of the endocannabinoid system by THC led to changes in neuronal development and homeostasis, pointing out the role of the endogenous cannabinoid system in neurodevelopment ( Viveros et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CB1Rs play a critical role in neuronal development due to their ability to modulate the release of neurotransmitters and expression, establishment of synaptic connection ( Kano et al, 2009 ), and epigenetic regulation ( Prini et al, 2018 ). The pharmacological exogenous manipulation of the endocannabinoid system by THC led to changes in neuronal development and homeostasis, pointing out the role of the endogenous cannabinoid system in neurodevelopment ( Viveros et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, plasma concentrations of THC-COOH were highest at 30, 60, 90 and 240 min compared to 15 min, reaching average peak levels of ~60 ng/mL, about 9 times higher than inhalation levels. Along these lines, previous studies have also shown peak THC-COOH concentrations at later timepoints (60-120 min) following injection in rats (Torrens et al, 2020) and inhalation in humans (Huestis et al, 1992). Further, given that plasma 11-OH-THC concentrations were higher following injection, and 11-OH-THC is the metabolic precursor of THC-COOH, it is not surprising that THC-COOH follows the same pattern.…”
Section: Thc-cooh Levels In Plasma and Brainmentioning
confidence: 58%
“…Rodent studies utilizing THC injections allow for control over both dose and timing; however, peak plasma THC concentrations are found at a slightly later timepoint following administration than with respect to inhalation (Javadi-Paydar et al, 2017; Nguyen et al, 2016; Taffe et al, 2020; Torrens et al, 2020). Further, clearance of THC from plasma following IP injections is much slower, with concentrations still roughly 65% of peak at 60 min and 50% at 120 min (Torrens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations